1999
DOI: 10.1073/pnas.96.13.7439
|View full text |Cite
|
Sign up to set email alerts
|

Induction of differentiation of pre-NKT cells to mature Vα14 NKT cells by granulocyte/macrophage colony-stimulating factor

Abstract: Besides their unique developmental properties, V␣14 NKT cells are shown to recognize glycolipid antigens in the context with a monomorphic CD1d (6, 7), whose mode of antigen recognition is entirely distinct from that of conventional T cells that recognize peptide antigens in association with the MHC, which is polymorphic in nature. Therefore, NKT cells seem to constitute a novel immune system mainly against glycolipid antigens. Moreover, V␣24J␣Q T cells, a human counterpart for V␣14 NKT cells, have been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 29 publications
1
22
1
Order By: Relevance
“…In the current study, we found that injection of mice with poly(I-C), a well-known and commonly used inducer of IFN-␣/␤, also caused a substantial loss of NKT cells ( (34,39), and IL-15 can induce the generation of pre-NKT cells into mature NKT cells (52), making it unlikely that an increase in IL-15 would cause a selective loss of NKT cells. IL-12 has been reported to cause a rapid reduction in NKT cells (18).…”
Section: Discussionmentioning
confidence: 91%
“…In the current study, we found that injection of mice with poly(I-C), a well-known and commonly used inducer of IFN-␣/␤, also caused a substantial loss of NKT cells ( (34,39), and IL-15 can induce the generation of pre-NKT cells into mature NKT cells (52), making it unlikely that an increase in IL-15 would cause a selective loss of NKT cells. IL-12 has been reported to cause a rapid reduction in NKT cells (18).…”
Section: Discussionmentioning
confidence: 91%
“…This may be due to incomplete depletion of CD8 ϩ T cells by in vivo administration of anti-CD8 mAb. NK cells (13,35), NK T cells (36,37), and a significant fraction of ␥␦ T cells (26, 27, 38 -42) are also reported to respond to IL-15. Thus, early production of IFN-␥ by these cells, besides CD8 ϩ T cells, may be also responsible for the impaired Th2 responses in IL-15-Tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF and GM-CSF are cytokines produced by activated T cells, macrophages, endothelial cells, and stromal fibroblasts that act on bone marrow to increase the production of inflammatory leukocytes (21). GM-CSF was reported to be a critical molecule for the initiation of TCR gene rearrangement in V␣14 NKT cells during the development of these lymphocytes (22). It was reported that mRNA of the mouse G-CSF receptor was expressed in mouse NKT cells (23).…”
Section: Discussionmentioning
confidence: 99%